Coaching by Age: An Analysis of Coaches’ Paternalistic Leadership on Youth Athletes’ Organizational Citizenship Behavior in China - Li, Juan; Li, Sitan; Hu, Jianbo; Chen, Ruichang (Frontiers in Psychology, 2021)
Based on social cognitive theory, we studied the relationship between coaches’ paternalistic leadership and youth athletes’ organizational citizenship behavior, and the mediation effect of athletes’ trust in coaches, in China. This age-specific research was conducted among more than 2,000 Chinese youth football players. Overall, 758 youth football players aged 13–18 years completed a self-report questionnaire. The results showed that the three dimensions of the coaches’ paternalistic leadership have different relationships with organizational citizenship behavior, and the differences were due to differences in athletes’ age. Additionally, we have verified the mediating role of trust in this study. Our research conclusions are of great significance to the study of Chinese youth football as in-depth research can provide a deeper and more precise understanding of the relationship between paternalistic leadership and the organizational citizenship behavior of Chinese youth football players.This study expands the literature on social cognitive theory and sheds light on the relationship between coach leadership and athlete organizational citizenship behavior by providing extensive evidence.